1973
DOI: 10.1182/blood.v42.6.935.935
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence the Appearance of Central Nervous System Leukemia

Abstract: At present, central nervous system (CNS) leukemia is one of the principal causes for termination of complete remission in acute lymphocytic leukemia (ALL). The factors which influence the increase of CNS infiltration have been studied comparing different parameters (age, initial peripheral WBC count, type of leukemia, and presence or absence of initial organomegaly) to determine the leukemia population with highest risk of developing this syndrome. A total of 127 cases of acute lymphoid leukemia (ALL) (98 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Evans et al (52) reported the frequency of CNS leukemia to be 25% in ANLL and 56% in ALL. Their data and that of others (47) indicate that the frequency per unit time was similar in both types and that the frequency was directly related to the duration of survival. Nies et al (53) observed an increasing frequency of CNS leukemia during the 1953-1963 decade of 25-42% in ALL and 4-12% in ANLL.…”
Section: Cns Leukemiamentioning
confidence: 68%
See 2 more Smart Citations
“…Evans et al (52) reported the frequency of CNS leukemia to be 25% in ANLL and 56% in ALL. Their data and that of others (47) indicate that the frequency per unit time was similar in both types and that the frequency was directly related to the duration of survival. Nies et al (53) observed an increasing frequency of CNS leukemia during the 1953-1963 decade of 25-42% in ALL and 4-12% in ANLL.…”
Section: Cns Leukemiamentioning
confidence: 68%
“…While the actual frequencies span a broad range, there is general agreement that CNS leukemia is diagnosed more often in ALL than in ANLL (34,(47)(48)(49) and more often in children than in adults with either cell type (28,33,34,47,50). Among adults with ALL, however, the frequency of CNS leukemia may not differ with age (49).…”
Section: Cns Leukemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Age is an important risk factor, with young children and infants more likely to experience CNS relapse. 6,9 Mature B-cell ALL and T-cell ALL are known to have an increased risk of CNS disease, both at presentation and relapse. Specific risk factors in children include: (i) high presenting leucocyte count (> 50 or > 100 × 10 9 /L, depending on the series), (ii) thrombocytopenia, (iii) lymphadenopathy and (iv) hepatosplenomegaly.…”
Section: Acute Lymphoblastic Leukaemia Biology and Risk Factors For Cmentioning
confidence: 99%
“…Specific risk factors in children include: (i) high presenting leucocyte count (> 50 or > 100 × 10 9 /L, depending on the series), (ii) thrombocytopenia, (iii) lymphadenopathy and (iv) hepatosplenomegaly. 9 In adults, high serum lactate dehydrogenase (LDH) and high proliferative index (i.e. cells in S (DNA synthesis) + G 2 (second cell growth) + M (mitosis) compartments of the cell cycle > 14%) are significant independent risk factors.…”
Section: Acute Lymphoblastic Leukaemia Biology and Risk Factors For Cmentioning
confidence: 99%